PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN KONSUMEN MENGUNJUNGI PARIWISATA PULAU CUBADAK DI TARUSAN PESISIR SELATAN - Pebrinalda, Yani - (Pendidikan Ekonomi, 2014)
Tourism canprovidea positiveimpactin the effortto contribute to therevenue of the country. The indicators usedforthe tourismindustrycan besaid to be successfulwith the increasingnumber of visitors. The strategy usedtoincrease thenumber of visitsone of whichisthe application ofmarketing mix. Based on the analysisof datasimultaneouslyit is known thatthe effect ofthe variableproduct, price, promotion, location, people, processandphysical evidencehave asignificant influence on thedecisionto visitthe attractionsin Pulau CubadakTarusanPesir selatan.The results showedthat: first,producthas positive influence onconsumer decisionvisiting Pulau Cubadak, which isindicatedby the value ofthe coefficientof0.378. Value ofthis coefficientis significant becausetcountfor4,036>ttable of1.68385. Second,Pricehas positive influence onconsumer decisionCubadakvisiting the island, which isindicatedby the value ofthe coefficientof0.129. Value ofthis coefficientis not significantbecausetcountof1.993>ttable of1.68385. Third,The place hasa positive influence onconsumer decisionvisiting Pulau Cubadak, which isindicatedby the value ofthe coefficientof0.162. Value ofthis coefficientis significant becausetcountfor2,297>ttable of1.68385. Fourth,Promotionshas a positive influence onconsumer decisionin visiting Pulau Cubadak, which isindicatedby the value ofthe coefficientof0.180. Value ofthis coefficientis not significantbecause the valueof2.446tcount> ttableat1.68385. Fifth,the Person haspositive influence onconsumer decisionin visiting Pulau Cubadak, which isindicatedby the value ofthe coefficientof0.213. Value ofthis coefficientis not significantbecausetcountof2.481>ttable of1.68385. Sixth,Processhas positive influence onconsumer decisionin visiting Pulau Cubadak, which isindicatedby the coefficientvalue of0.197. Value ofthis coefficientis significant becausetcountfor2,185>ttable of1.68385. Seventh,thephysicalevidencehas positive effect on the consumers decision to visitPulau Cubadak, indicatedby the coefficientvalue of0.129. Value ofthis coefficientis not significantbecause the valueof2.724tcount> ttableat1.68385. Eighth,Product, Price, Place, Process, People, Process, Physical evidencesimultaneously havepositive and significant influenceonconsumer decisionsin visiting Pulau CubadakinTarusan Pesisir SelatanWhere theobtained valueof Fcount102 639>Ftable2.53andsignificantvalue0.000<Î± =0.05. Thismeans thatH0is rejectedandHa accepted